Small is big in ICT: The impact of R&D on productivity. (February 2020) - Koutroumpis, Pantelis; Leiponen, Aija; Thomas, Llewellyn D.W.
Abstract: We examine the contribution of R&D to firm productivity in a large panel of European firms and study its variation with the age, size, and sub-sector of firms. We find that R&D capital in ICT firms has a larger effect on revenue when compared to non-ICT firms. At the firm level, our results suggest that, surprisingly, smaller and older ICT firms benefit the most from R&D. Small but mature ICT firms are likely to dominate market niches, and small size may enable them to be flexible and adaptable which helps them respond to technological opportunities to develop innovative products and services. This has important implications for public policy based upon firm age. Highlights: R&D capital in ICT firms has a larger effect on revenue when compared to non-ICT firms. Smaller and older ICT firms benefit the most from R&D capital. Small but mature ICT firms are likely to dominate market niches.